Conservation strategies for European crop wild relative and landrace diversity: Joint PGR Secure/ECPGR Workshop, 7-9 September 2011, Palanga Lithuania - Kell, S.; Negri, V.; Torricelli, R.; Maxted, N.; Maggioni, L.; Fielder, H. (2011)
The joint PGR Secure/European Cooperative Programme for Plant Genetic Resources (ECPGR) workshop, ‘Conservation strategies for European crop wild relative and landrace diversity’, was convened in Palanga, Lithuania from 7‒9 September 2011 to discuss and agree a strategic approach to European and national crop wild relative (CWR) and landrace (LR) conservation. The ultimate aim is to ensure the systematic conservation of European plant genetic resources for food and agriculture (PGRFA) which are important for food security and the European economy. The workshop addressed five primary topics: 1) production of National Inventories (NIs), 2) taxon prioritization, diversity and gap analysis, and threat assessment, 3) data collection, management and exchange, 4) linking conservation to use, 5) development and implementation of national CWR and LR conservation strategies by the ECPGR Network members. The workshop comprised a series of presentations and discussion sessions on the state of the art of CWR and LR conservation in Europe and available approaches and methods. Participants shared knowledge on current national activities, discussed the practicalities of developing national CWR and LR conservation strategies, and agreed on the way forward. The workshop wasstructured around three plenary sessions (introductory, interim and final reporting) and three working group sessions (CWR conservation, LR conservation, and information management).